Turning Adversity into Opportunity: A Black Woman’s Journey into Academia - Ndlovu, Nokulunga Sithabile (South African Journal of Higher Education, 2016)
This article is a contribution to the stories of black women educators in schools and higher education institutions in South Africa as we have responded to a variety of challenges in our journeys into academia. It is an auto-ethnographic account in which I have borrowed concepts from sociology to help me analyse my experiences in two educational fields or contexts (a high school and a university) which have contributed to the constitution of a habitus characterised by resilience1 and assertiveness2. In this auto-ethnography I focus on the challenges I have faced, how my habitus has informed the choices I have made in response to these challenges and how, as I have tried to figure out what actions to take I have been able to survive in the sometimes trying circumstances presented by the fields. My story is in three parts: (i) my experiences as a Zulu First Additional language teacher in a previously white suburban high school in which there were no materials available for teaching Zulu at this level; (ii) my largely positive experiences as a student in a B Ed Honours degree programme which enabled me to respond to some of the challenges of this high school teaching context;(iii) my experiences as a lecturer in the Wits School of Education with responsibility for teaching (successively) Zulu Additional Language and ICT in Education courses, while also undertaking research in the latter area – experiences in which the support of a mentor has played a key role. I conclude by making explicit the impact of the interactions between my habitus and the experiences I have had in the two fields as I have made choices that have contributed to my on-going development as an academic. Keywords: habitus; field; options; resilience; assertiveness